Influence of individual factors on thermal satisfaction of the elderly in free running environments. (1st May 2017) - Jiao, Yu; Yu, Hang; Wang, Zi; Wei, Qi; Yu, Yifan
Abstract: It is important to identify individual factors that influence the thermal satisfaction of the elderly in their homes. This paper presents a field survey and thermal environment investigation in elderly facilities in Shanghai, China. In this study, 17 elderly facilities with 42 free running buildings and 672 healthy elderly people over 70 were randomly selected. Questionnaire surveys and thermal environmental parameter measurements were taken simultaneously. Logistics multiple regression models were established for winter and summer conditions, and influences of individual factors on thermal satisfaction of the elderly in free running environments were analyzed. Results indicated that the factors affecting the thermal satisfaction of the elderly had distinct seasonal differences. 'Satisfaction on wind environment' influenced elderly thermal satisfaction both in winter and summer season. In addition, the influencing factors of the thermal satisfaction also included: "time indoors", "influence of sickness" in winter season and "sleeping regularly" in summer season. Furthermore, the results of this study may be a useful reference when managing or designing thermally comfortable homes for the elderly. Highlights: Factors affecting thermal satisfaction of elderly had seasonal differences. 'Satisfaction on wind environment' influenced both in winter and summer season. This study may be a useful reference when managing or designing elderly homes.